Students Satisfaction Towards Cafeteria in University Campus – A Case Study: Students Satisfaction Towards Cafeteria in University Campus - Misiran, Masnita; Md Yusof, Zahayu; Sapiri, Hasimah; Abdullah, Ilyani (Journal of Statistical Modeling and Analytics (JOSMA), 2022)
Food industry plays a crucial role as one of the critical sectors in every country. A restaurant is a part of food industry which serves foods and drinks to customers in return for money. Customer satisfaction is a measurement of service or product supplied by a restaurant whether it unmeet, meet, or surpass customer satisfaction. As restaurants in campus or college cafeteria are the main service provider for students that resides inside a university, it is necessary to regularly maintain their quality as to ensure that the food consumed are of good quality, nutritious, and hygienic. This problem has been faced by all university foodservice management in Malaysia. In response to this problem, this dissatisfaction leads the students to refuse having their meals inside campus. Therefore, this study used structural equation modelling to identify the factors which significantly affect students’ satisfaction toward one cafeteria in a university and determine the relationship among the factors and their impact on students’ satisfaction. Results showed there are two factors which are service quality and varieties of menu show a significant positive influence towards students’ satisfaction. Therefore, this finding suggested that the college cafeteria should put more effort on the service quality that they provided.